Comparison of blade designs in paddle sports - Ritchie, A. C.; Selamat, M. F. B. (Sports Technology, 2010)
The design of paddles used in canoe racing has been the subject of considerable research, with specialised designs for flat water racing (canoe sprint), surf and white water canoeing. The paddles used in Asian boat racing remain much closer to traditional designs. To examine the effect of this development, the pressure distribution and coefficient of drag for canoe paddle blades are compared to the paddle designs used in Asian boat races. The pressure distribution on the face of the paddle was examined using computational fluid dynamics (CFD), and drag forces and the coefficient of drag were examined experimentally in a water tunnel. The results show that although the CFD predicts considerable variation in performance, experimental testing showed much lower variation in the performance of the paddles. The results show that the modern macon type paddle would be easiest to control, and the leaf shaped paddle used in snakeboat racing would have the highest coefficient of drag.